Use of Logistic Regression Approach to Determine the Effective Factors Causing Renal Failure Disease - Shappot, Sami Jabbar; Gorgees, Hazim Mansoor (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The main goal of this research is to determine the impact of some variables that we believe that they are important to cause renal failuredisease by using logistic regression approach.The study includes eight explanatory variables and the response variable represented by (Infected,uninfected).The statistical program SPSS is used to proform the required calculations